Occurrence of South American fur seals Arctocephalus australis (Zimmermann, 1783) in San Matías Gulf, Patagonia, Argentina - Svendsen, Guillermo (2013)
The South American fur seal, Arctocephalus australis (SAFS) population suffered a drastic reduction due to commercial exploitation during the eighteenth and nineteenth centuries. In the last decades a population recovery was detected on the Atlantic region. However, in this region, many aspects of the ecology of the SAFS, such as the post-reproductive dispersal of individuals, the location of feeding areas, and the migration routes between colonies in the southern border of its distribution. are still unknown. Here, we report for the first time the occupation of San Matías Gulf (SMG, Northern Patagonia, Argentina) by this species. We found that more than 1,600 SAFS used SMG between May and October (post-reproductive season) and detected a non-reproductive colony on Lobos Islet (41°24´S, 65°03´W). The presence of SAFS in SMG is recent and would be associated with an increase of the population. The importance of SMG in the ecology of SAFS seems to lie on three factors: the strategic location in the geographic context of its potential migration routes, the physical environment suitable for coastal settlements, and the availability of food resources.